Tumor Microenvironment in Ovarian Cancer: Function and Therapeutic Strategy - Yang, Yanfei; Yang, Yang; Yang, Jing; Zhao, Xia; Wei, Xiawei (Frontiers in Cell and Developmental Biology, 2020)
Ovarian cancer is one of the leading causes of death in patients with gynecological malignancy. Despite optimal cytoreductive surgery and platinum-based chemotherapy, ovarian cancer disseminates and relapses frequently, with poor prognosis. Hence, it is urgent to find new targeted therapies for ovarian cancer. Recently, the tumor microenvironment has been reported to play a vital role in the tumorigenesis of ovarian cancer, especially with discoveries from genome-, transcriptome- and proteome-wide studies; thus tumor microenvironment may present potential therapeutic target for ovarian cancer. Here, we review the interactions between the tumor microenvironment and ovarian cancer and various therapies targeting the tumor environment.